Micropartículas circulantes e geração de trombina em pacientes com Leucemia Linfocítica Crônica - Aline Lucia Menezes (2016)
Chronic Lymphocytic Leukemia (CLL) is a disease with higher prevalence in the elderly, characterized by B lymphocytes accumulation in the body. The survival of patients is about 10 years, but the prognosis is variable and some patients have short survival. Therefore, it is important to identify early individuals who will present rapidly disease progression and that can benefit from the most appropriate treatment protocols. Researches emphasizing on the role of the microparticles (MPs), from different cell sources, in the pathogenesis of many diseases have been conducted. These MPs consist of cell membrane fragments or cytoplasm of their cells of origin. MPs primarily derived platelets is elevated in thromboembolic disorders and there is a clear association between cancer and coagulation. The aim of this study was to evaluate the hemostatic profile of patients with CLL by quantifying plasma circulating MPs and the thrombin generation potential (TG) and its correlation with disease progression. Thirty five patients diagnosed with CLL, selected in the Hematology Service of the Clinical Hospital, Federal University of Minas Gerais were included in this study. The same analyzes were performed on 35 apparently and clinically healthy subjects (control group). The MPs derived from endothelial cells (MPEs), MPs of B lymphocytes (MPLs) and platelet MPs (MPPs) analysis was performed by flow cytometry and the evaluation of hemostatic profile was performed using Thrombin Generation test (TG) by the CAT method. It was observed significantly increased levels of MPEs[132.1 (78.6 to 199.1)] when compared patients and controls [81.6 (53.1 to 121.0) p = 0.002], respectively. The same was observed for MPLs[142.1 (93.7 to 203.1)] compared to controls [85.2 (63.4 to 115.9), p <0.001] and MPPs [134.8 (85.7 to 183.1)], control group = [81.2 (52.8 to 118.9), p = 0.003]. When the patients were stratified according to the Binet staging of the disease significant differences were observed (p <0.05): Binet A versus controls for MPEs [149.8 (75.3 to 212 5)], MPLs [145.2 (91.9 to 235.6)] and MPPs [148.1 (82.2 to 202.1)]. On the other hand, the potential of thrombin generation was lower in CLL [1453.00 (1176.33 to 1602.57)] compared to the controls [1577.38 (1326.20 to 1816.95), p = 0.031], especially in moderate and severe cases classified as Binet B + C [1216.54 (1130.47 to 1540.15), p = 0.009]. The increased number of MPs in CLL indicates that microparticulation may result in the pathogenesis of the disease itself, and not necessarily related to disease progression. On the other hand, the TG potential decreased in CLL compared to controls, especially in moderate and severe cases, and this data suggest that the disease might affect not only the number of platelets, but also other factors of importance in hemostatic system, making the patient predisposed to hemorrhages events than thrombotic.